Evaluation of the Efficacy and Accuracy of Super-Flexible Three-Dimensional Heart Models of Congenital Heart Disease Made via Stereolithography Printing and Vacuum Casting: A Multicenter Clinical Trial - Isao Shiraishi; Masaaki Yamagishi; Takaya Hoashi; Yoshiaki Kato; Shigemitsu Iwai; Hajime Ichikawa; Tatsuya Nishii; Hiroyuki Yamagishi; Satoshi Yasukochi; Masaaki Kawada; Takaaki Suzuki; Takeshi Shinkawa; et al. (Journal of Cardiovascular Development and Disease)
Three-dimensional (3D) printing is an advanced technology for accurately understanding anatomy and supporting the successful surgical management of complex congenital heart disease (CHD). We aimed to evaluate whether our super-flexible 3D heart models could facilitate preoperative decision-making and surgical simulation for complex CHD. The super-flexible heart models were fabricated by stereolithography 3D printing of the internal and external contours of the heart from cardiac computed tomography (CT) data, followed by vacuum casting with a polyurethane material similar in elasticity to a child’s heart. Nineteen pediatric patients with complex CHD were enrolled (median age, 10 months). The primary endpoint was defined as the percentage of patients rated as “essential” on the surgeons’ postoperative 5-point Likert scale. The accuracy of the models was validated by a non-destructive method using industrial CT. The super-flexible heart models allowed detailed anatomical diagnosis and simulated surgery with incisions and sutures. Thirteen patients (68.4%) were classified as “essential” by the primary surgeons after surgery, with a 95% confidence interval of 43.4–87.4%, meeting the primary endpoint. The product error within 90% of the total external and internal surfaces was 0.54 ± 0.21 mm. The super-flexible 3D heart models are accurate, reliable, and useful tools to assist surgeons in decision-making and allow for preoperative simulation in CHD.